ANALISA PERILAKU MEKANIK KOMPOSITSERAT KAPUK RANDU MENGGUNAKANMATRIK POLYESTER - Syamsul Arif Sarifudin; . Tarkono; . Sugiyanto (Jurnal Ilmiah Teknik Mesin, 2013)
The background research is the development of science and technology in the field of materials engineering and the demands off indinga new breakthrough in the provision of high quality materials and environmentally friendly. Composite materials of natural fibers that are more light weight, malleable, corrosion resistance, low price andeasy to obtain. This study uses materials such aspolyesterresin, and a catalyst Randu Kapok fiber. Randomly arranged fibers incomposites with various volume fractions of 15%, 25%, 35%. Making way press mold, bending tests were conducted with a reference standard ASTM D790-02, tensile testing standard ASTM D-638. Testing through the process of tensile and bending tests to determine the mechanical properties of the composite. Greatest tension obtained in the composite with 35% volume fractionis equal to 3,8046 MPa while the largest bending strength of the composite obtained from volume fraction 15% at 84MPa. Void formed causing the load can be held by thematrixis reduced due tolack of homogenan specimens.Keywords: Composite, Kapok Fiber, Polyester, Mechanic strength, Tensile Test and dan BendingTest.